1986
DOI: 10.1002/jor.1100040106
|View full text |Cite
|
Sign up to set email alerts
|

Computerized tomography of proximal femoral trabecular patterns

Abstract: A comprehensive imaging and pathologic investigation utilizing patients and cadaver material was performed in order to identify the normal trabecular pattern of the proximal femur and to assess alterations in this pattern in various disorders. Patients and specimens were studied with computed tomography (CT), including three-dimensional CT image reconstruction in selected cases and plain film radiography. The CT imaging of the proximal femur provides insight into the dynamic state of bone in this region. Despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 30 publications
2
11
0
1
Order By: Relevance
“…Previous studies have indicated that the geometric redistribution ofbone tissue is an important means of preserving bone strength and rigidity under conditions of decreasing bone quality (23)(24)(25)(26). Moreover, age-related geometrical remodeling of the skeleton appears to be a characteristic of both trabecular (27,28) and cortical bone (29)(30)(31), and may be a feature of disease processes such as osteoporosis (32). The results of this study extend these observations to heritable diseases associated with skeletal fragility such as osteogenesis imperfecta type I.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies have indicated that the geometric redistribution ofbone tissue is an important means of preserving bone strength and rigidity under conditions of decreasing bone quality (23)(24)(25)(26). Moreover, age-related geometrical remodeling of the skeleton appears to be a characteristic of both trabecular (27,28) and cortical bone (29)(30)(31), and may be a feature of disease processes such as osteoporosis (32). The results of this study extend these observations to heritable diseases associated with skeletal fragility such as osteogenesis imperfecta type I.…”
Section: Discussionsupporting
confidence: 62%
“…Previous work has revealed that, in osteoarthritis, there is thickening of trabeculae (Kerr et al, 1986;Grynpas et al, 1991) and hence an increase in the amount of bone within the subchondral zone of the weight-bearing region (Kerr et al, 1986;Oettmeier and Abendroth, 1989;Crane et al, 1990;Fazzalari et al, 1992), whereas a loss of bone has been noted in the non-weight-bearing region (Fazzalari et al, 1992). The exact mechanisms that bring about the changes in bone morphology are unclear, but changes in osteoblastic (Jeffery, 1973;Xu and Chai, 1992) and os-*Correspondence to: Dr. Stuart W. McDonald, Laboratory of Human Anatomy, University of Glasgow, Glasgow, G12 8QQ, UK.…”
Section: Introductionmentioning
confidence: 99%
“…If multiple brown tumours are found radiographically in a patient not known to have hyperparathyroidism, osteoporosis makes vertebrae appear particularly lucent, and if there is a vertebral compression fracture, it is often difficult to be certain whether there is any underlying bone lesion. Patients with severe, chronic osteoporosis may develop reenforced trabeculae in the femoral neck which simulates cartilage tumour matrix or a bone infarct (Kerr et al 1986). Loosers zones in osteomalacia have a relatively specific appearance and are not usually mistaken for tumours, although if they occur in an unusual site this may lead to diagnostic difficulties.…”
Section: Metabolic Disordersmentioning
confidence: 99%